2019
DOI: 10.3390/ijerph16081475
|View full text |Cite
|
Sign up to set email alerts
|

Different Associations between DC-SIGN Promoter-336G/A (rs4804803) Polymorphism with Severe Dengue in Asians and South-Central Americans: a Meta-Analysis

Abstract: Objective: This study was conducted to identify the association between rs4804803 polymorphism in DC-SIGN with the susceptibility of severe dengue. Methods: A comprehensive search was conducted to identify all eligible papers in PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and Google Scholar. Odds ratios (ORs) and corresponding 95% confidence intervals (95% CIs) were used to assess the association. Subgroup analyses were performed by ethnicity. Sensitivity analyses were performed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…They concluded that DC-SIGN-336 SNP was strongly associated with severe DF while a few other studies found no association of DC-SIGN-336A/G SNP with dengue infection. [27][28][29] It is well established that the relationship between an SNP and human disease is rarely forthright and complicating factors like linkage, population-specific genetic differences, epigenetic changes, and environmental factors do come into play. Therefore the discrepancy between these studies regarding protection for or no association of the G allele with DF may result from the heterogeneous distribution of the G allele among studied populations, other population-specific genetic differences, differences in clinical categories compared and/or sampling strategies, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that DC-SIGN-336 SNP was strongly associated with severe DF while a few other studies found no association of DC-SIGN-336A/G SNP with dengue infection. [27][28][29] It is well established that the relationship between an SNP and human disease is rarely forthright and complicating factors like linkage, population-specific genetic differences, epigenetic changes, and environmental factors do come into play. Therefore the discrepancy between these studies regarding protection for or no association of the G allele with DF may result from the heterogeneous distribution of the G allele among studied populations, other population-specific genetic differences, differences in clinical categories compared and/or sampling strategies, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…48 Heparan sulfate receptors are implicated in the pathogenesis of several orthoflaviviruses enhancing viral entry efficiency into host cells, 49 while C-type lectin receptors (CLR) such as mannose receptors Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN), and its homolog, DC-SIGN-related (L-SIGN), and C-type lectin domain family 5 member A (CLE5A) have been associated with DENV entry and propagation under in vitro studies, with strong correlation between polymorphisms in DC-SIGN receptors and occurrence of dengue hemorrhagic syndrome with different patterns of inheritance in different regions of the world. 50 Moreover, laminin receptors are involved in the DENV-1 cell entry in the liver, 51 and phosphatidylserine receptors are able to interact with this component in the viral membrane and mediate internalization of DENV. 48,52 Other molecules involved in DENV entrance in host cells include integrins, Claudin-1, and scavenger receptor class b type I.…”
Section: Denvmentioning
confidence: 99%
“…(28,29) In addition, other studies associated these polymorphisms with the severity of tuberculosis, (30) hepatitis C, (31) severe acute respiratory syndrome (32) and dengue fever. (33,34) Considering that the recognition of M. leprae involves DC-SIGN, but polymorphisms in this gene were not associated with leprosy susceptibility, (22) we investigated the association of single nucleotide variants (SNVs) in the promoter region of the CD209 gene with clinical forms of leprosy in the Brazilian population. In addition, we investigated the functional effects of these polymorphisms on the response to M. leprae.…”
mentioning
confidence: 99%